Positive impact of self-assessment first year Experience on academic achievement among International students - Irma Wani Othman; Kamsilawati Kamlun; Wardatul Akmam Din; Ameiruel Azwan Ab Aziz (Global Academic Excellence, 2022)
The academic aspect plays a vital role as a 'transformative' element in bringing change into the life of each individual. One of the main goals of students continuing their studies abroad is to obtain a high-quality education. The firstyear experience is considered an important phase involving self-assimilation, emotional change, cultural shock and social values that can influence the academic achievement of international students. The discussion of this paper elucidates the factors that contribute to the more meaningful first-year experience differences by comparing the process of self-assimilation and academic achievement of international students. In-depth interviews with 40 international students from four Malaysian public universities were conducted using a qualitative method approach that used objective sampling techniques. The findings lead to a self-reflection on the nature of international students, which is expressed through a narrative outpouring of emotions that describe the excitement, desire, and hope. The elements of transformation and selfassimilation of students in this study are interconnected with (i) the reputation of Malaysian public universities as a prestigious educational destination, (ii) the quality of a more comprehensive and 'versatile' higher education system, (iii) the flexibility and dynamics of the academic programs offered, and (iv) contemporary and ‘market driven' academic programs. The empirical data from this study is hoped to be useful information for the university's human resource management, which relies heavily on international student enrolment. This effort is in line with Malaysia's National Strategic Plan for Higher